Государственный преступник: [роман] / Евгений Сухов - Сухов Евгений Евгеньевич (Я - вор в законе, 2007)
Экземпляры: аб. (2007) / Инвентарный номер: 51326 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44